Analisis Proses Bisnis Dalam Meningkatkan Produksi Dan Penjualan Pada Umkm Tempe Manabaya Di Parakanmuncang, Kabupaten Sumedang - Hasanawi Masturi; Jajang Suherman (Journal of Innovation Research and Knowledge, 2026)
Tempe Manabaya Micro, Small, and Medium Enterprise (MSME) in Parakanmuncang, Sumedang Regency, plays an important role in the local economy but still faces various challenges in business process management that affect production efficiency and sales performance. The main challenges include non-standardized production workflows, suboptimal raw material inventory control, basic operational record-keeping, and limited utilization of digital marketing. This study aims to analyze the existing business processes and identify opportunities for improvement to enhance productivity and sales. The study employed a qualitative approach using a case study method. Data were collected through observation, in-depth interviews, and documentation, and were subsequently analyzed using business process analysis to map key activities and identify areas requiring improvement. The results indicate that streamlining workflows, standardizing production processes, strengthening inventory control, and implementing digital marketing can improve operational efficiency, reduce processing time, increase production capacity, and expand market reach. These findings confirm that business process analysis is an effective approach to enhancing the competitiveness and sustainability of MSMEs through more efficient and value-added operational management